Redox processes in sodium vanadium phosphate cathodes – insights from operando magnetometry. Issue 36 (4th September 2019) - Klinser, Gregor; Zettl, Roman; Wilkening, Martin; Krenn, Heinz; Hanzu, Ilie; Würschum, Roland
Abstract : Oxidation processes and electrode–electrolyte interphase formation upon battery cycling have been revealed by operando magnetic susceptibility measurements. Abstract : Operando magnetic susceptibility measurements of sodium ion cathode materials during repetitive electrochemical cycling enable a continuous and bulk sensitive monitoring of the transition metal oxidation states. Such measurements on Na x V2 (PO4 )3 identified vanadium to be the only ion undergoing oxidation/reduction processes upon battery operation. For the initial battery charging–discharging cycle as well as for the first cycle after prolonged room temperature storage, however, peculiarities within the magnetic susceptibility measurements indicate parasitic side reactions, likely on the cathode surface.